Kesan langsung prinsip transformasi perkhidmatan ke atas kualiti perkhidmatan di sektor awam - Ismail, Zarina; Md. Salleh, Salniza; Ali, Juhary (2013)
The purpose of this study is to investigate the relationship between service transformational principle (creativity and innovation, decision-making, value of money and intergrity) and the service quality of the Ministry of Health Malaysia (MOH).A total of 700 questionnaires were distributed, only 339 questionnaires collected and can be used for analysis.Data collected was analysed using Descriptive Analysis, Pearson Correlation Analysis and Regression Analysis.The findings of this study indicated that there was a significant relationship between creativity and innovation, decision-making, valuefor-money and integrity and the service quality of MOH.